Three times lucky - Turnage, Sheila (New York : Puffin Books, 2014)
Washed ashore as a baby in tiny Tupelo Landing, North Carolina, Mo LoBeau, now eleven, and her best friend Dale turn detective when the amnesiac Colonel, owner of a café and co-parent of Mo with his cook, Miss Lana, seems implicated in a murder.
Winner of the Newberry honor award.
Keywords: Children's stories; Detective and mystery fiction